2012
DOI: 10.1089/neu.2011.2018
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of the Monro-Kellie Doctrine: Is It Possible?

Abstract: The Monro-Kellie doctrine describes the principle of homeostatic intracerebral volume regulation, which stipulates that the total volume of the parenchyma, cerebrospinal fluid, and blood remains constant. Hypothetically, a slow shift (e.g., brain edema development) in the irregular vasomotion-driven exchanges of these compartmental volumes may lead to increased intracranial hypertension. To evaluate this paradigm in a clinical setting and measure the processes involved in the regulation of systemic intracrania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 37 publications
0
34
0
5
Order By: Relevance
“…11,37 It remains a topic of debate as to how the various indices of pulsatile ICP analyzed with modern computerized methods are associated with the intracranial pressure-volume reserve capacity. 5,7,21,24 Hence, further studies are needed to determine the association between pulsatile ICP and ICE.…”
mentioning
confidence: 99%
“…11,37 It remains a topic of debate as to how the various indices of pulsatile ICP analyzed with modern computerized methods are associated with the intracranial pressure-volume reserve capacity. 5,7,21,24 Hence, further studies are needed to determine the association between pulsatile ICP and ICE.…”
mentioning
confidence: 99%
“…We used this approach to calculate new values of the electrical parameters because, according to the Monro-Kellie relation, the internal volume of the skull remains constant during the cardiac cycle, so the relative volumes of the brain, blood, and CSF should vary. These variations can be modelled either using elasticity theory [11], or by direct modification of the electrical parameters of the finite elements. The complexity of the mechanical model of the brain, which takes into account elasticity and fluid flow, is very high.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 10 recently reported that changes in intracranial venous, arterial, and CSF compartments could be mathematically estimated using serial analysis, allowing the calculation of a cerebral complacency index (CCI) as a correlation coefficient of changes in compartments. The authors Figure 2.…”
Section: Discussionmentioning
confidence: 99%